STUDI USAHA TANI KELAPA SAWIT PETANI DI DESA SALIKI KECAMATAN MUARA BADAK BERDASARKAN PRODUKSI TBS DAN HARGA SAWIT - Rizal Abdul Harisma Rizal; Sukariyan; Abdul Rasyid Zarta (Politeknik Pertanian Negeri Samarinda, 2021)
This research is based on the background that oil palm plantations are a form of community farming that cultivates oil palm plants with production in the form of fresh fruit bunches (FFB) as one of their sources of livelihood, although investment in oil palm plantations requires a relatively long period of time compared to oil palm plantations. with other plantation commodities. The purpose of this study was to determine the oil palm farming business in Saliki Village based on FFB production and palm oil prices. The data collection method used in this study is a qualitative method, which is a research that is used if the research factors cannot be quantified or cannot be calculated so that the variables cannot be expressed with numbers such as perceptions, opinions, assumptions and so on. According to qualitative research theory, in order for the research to be of really high quality, the data collected must be complete, namely primary data and secondary data. From the results of this study, it can be concluded that oil palm farming in Saliki Village based on the production of fresh fruit bunches and the price of palm oil really helps farmers increase their income from farming by selling large quantities of produce and high selling prices. The income they generate from oil palm plantations can meet their daily needs. In addition, the community (oil palm farmers) can buy vehicles, renovate and even build houses from the results of the oil palm plantations. The results of this study are to provide information to the community in Saliki Village in order to be able to improve oil palm farming.